Flood Control Measures in Northern India - Tiwari, K. M. (Indian Forester, 1955)
Causes of recent flood occurrence have been traced from historical, scientific, mythological and observational evidences. Sudden rush of water from catchment areas due to little obstruction and less carriage capacity of the rivers in the plains area due to silting up of their beds have been traced as the most potent causes of flood havoc. The remedy lies in afforesting the denuded and treeless Himalayan ridges constituting the catchment areas and construction of engineering structures such as dams, embankments, etc., in the plains area to regularise their course, for which concrete scheme has been suggested.